2005
DOI: 10.1007/s11046-004-7321-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological effect of the mycotoxins cyclopiazonic acid and T-2 toxin on broiler chicken

Abstract: Forty, newly hatched, unsexed broiler chicks were fed diets containing 10 ppm cyclopiazonic acid (CPA) and 1 ppm T-2 toxin (T2) either individually or in combination for 28 days to study the immunopathological effects. Lymphoid organs revealed lymphocytolysis and lymphoid depletion in all toxin fed birds. Thymic and splenic CD+4 and CD+8 lymphocytes decreased significantly (p<0.01) in toxin fed birds when compared to the control. Thymic CD+8 lymphocytes of T2 and CPA-T2 showed significant (p<0.01) decrease fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
3
40
0
1
Order By: Relevance
“…The exposure to the T-2 toxin causes leukopenia and cell depletion in lymphoid organs, it inhibits erythropoiesis in the bone marrow and spleen (Nagata et al 2001, Grizzle et al 2004, Parent-Massin 2004. T-2 intoxication can significantly impair antibody production (Niyo et al 1988, Kamalavenkatesh et al 2005, Li et al 2006a, it reduces the proliferative response of lymphocytes (Rafai et al 1995, Kamalavenkatesh et al 2005 and hinders the development of dendritic cells (Hymery et al 2006, Hymery et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The exposure to the T-2 toxin causes leukopenia and cell depletion in lymphoid organs, it inhibits erythropoiesis in the bone marrow and spleen (Nagata et al 2001, Grizzle et al 2004, Parent-Massin 2004. T-2 intoxication can significantly impair antibody production (Niyo et al 1988, Kamalavenkatesh et al 2005, Li et al 2006a, it reduces the proliferative response of lymphocytes (Rafai et al 1995, Kamalavenkatesh et al 2005 and hinders the development of dendritic cells (Hymery et al 2006, Hymery et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, comparison of these concentrations to those used in laboratory experiments suggested that these cranes could have been subject to chronic mycotoxic effects. These negative effects include growth retardation, tumor development, and immunotoxicity, thus increasing crane susceptibility to predation and disease (Carnaghan, 1965;Choudhury, 1971;Huff et al, 1986;Kamalavenkatesh et al, 2005). Moreover, although low mycotoxin concentrations do not cause morbidity in controlled laboratory settings, it might reduce the survival probability of wild species that rely on highly efficient metabolic systems to cope with extreme environments, such as winter conditions (Oberheu and Dabbert, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo foram utilizadas aves com 35 dias de idade, consideradas jovens. Analisando-se o papel de linfócitos T CD4 + e CD8 + no fornecimento de resposta imunológica contra infecções percebe-se que quando existe uma diminuição por diversos fatores, a suscetibilidade para a Salmonelose aumenta (Kamalavenkatesh et al 2005).…”
Section: Discussionunclassified